The influence of concomitant type 2 diabetes mellitus on the number of circulating progenitor cells in patients with ischemiccardiomyopathy - Tatiana Nikolaevna Kochegura (Endocrinology Research Centre, 2011)
Aim. To study effect of concomitant type 2 diabetes mellitus on the number of circulating progenitor cells (CPC) in patients with coronary heart disease(CHD) and postinfarction heart failure (ischemic cardiomyopathy).Methods. The number of CPC (CD34+ cells) was determined by flow cytophotometry in 47 patients with CHD including 14 with CHD + DM2; 12patients without CHD and DM2 made up the control grouP. Enzyme-linked immunosorbent assay was used to measure N-terminal precursor of brainnatriuretic peptide (NT-proBNP), immunoreactive insulin (IRI) and C-peptide levels. Results. The number of CPC in patients with ischemic cardiomyopathy without DM2 was 33.4% greater than in controls. In patients with cardiomyopathyand DM2 the number of CPC depended on the quality of diabetes compensation. It was lowest in case of decompensated DM2 (HbA1c=9.5?1.8%).In patients with compensated/subcompensated DM2 (HbA1c=6.8?0.3%) it was significantly higher than in controls and patients with ischemiccardiomyopathy without DM2 (mean 46.5 (p=0.006) and 40.0% (p=0.02) respectively). Conclusion. The number of CPC in peripheral blood of patients with ischemic cardiomyopathy and DM2 correlated with the level of DM compensation.It was lowest in patients with decompensated DM2 and exceeded the normal number in patients with CHD without DM2. The number of CPC inverselycorrelated with blood glucose level. Positive correlation of CPC number with IRI and C-peptide levels was documented in control subjects and patientswith CHD without DM2.